2010
DOI: 10.1002/gea.20309
|View full text |Cite
|
Sign up to set email alerts
|

Threatened archaeological, historic, and cultural resources of the Georgia Coast: Identification, prioritization and management using GIS technology

Abstract: Archaeological sites in beach and estuarine environments are continually threatened by diverse natural marine processes. Shoreline erosion, bluff retreat, and sea level rise all present potential for site destruction. Using historic maps, aerial imagery, and field survey methods in a GIS, 21 potentially significant archaeological sites on Georgia barrier islands were selected for determination of site-specific rates of shoreline change using a powerful, new, moving-boundary GIS analysis tool. A prioritized lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 11 publications
0
24
0
1
Order By: Relevance
“…Some recent studies conducted in Australia, Canada, U.K., and the U.S. found that climate adaptation prioritization is needed to make transparent decisions between what cultural resources to protect and preserve (for both current and future generations) and what cultural resources to release or "let go" e.g., [9,[58][59][60]. As such, prioritization decisions need to be informed by deliberation with multi-level actors about feasible strategies that integrate the significance of cultural resources with climate change vulnerabilities to ensure continued preservation of diverse heritage values and resources [61].…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies conducted in Australia, Canada, U.K., and the U.S. found that climate adaptation prioritization is needed to make transparent decisions between what cultural resources to protect and preserve (for both current and future generations) and what cultural resources to release or "let go" e.g., [9,[58][59][60]. As such, prioritization decisions need to be informed by deliberation with multi-level actors about feasible strategies that integrate the significance of cultural resources with climate change vulnerabilities to ensure continued preservation of diverse heritage values and resources [61].…”
Section: Discussionmentioning
confidence: 99%
“…Suffice it to say however that while there are limitations to this method, the approach does hold merit as a means of producing a generalized model of historical coastal change rates. For examples of similar methods applied in heritage management efforts elsewhere, see also : Radosavljevic et al (2015), Reeder et al (2012) and Robinson et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…The archaeological sites that are established along the coastlines environments are always threatened by shoreline erosion, sea wave storms, tsunamis and sea level rise [14]. In the case of the western Crete many different types of archaeological relics are close to the coast.…”
Section: Distance Of Archaeological Sites From Coastmentioning
confidence: 99%